Trends in nanotechnology and its potentialities to control plant pathogenic fungi: a review - Kutawa, Abdulaziz Bashir; Ahmad, Khairulmazmi; Ali, Asgar; Abdul Wahab, Mohd Aswad; Adamu, Abdullahi; Ismaila, Abubakar Abubakar; Gunasena, Mahesh Tiran; Rahman, Muhammad Ziaur; Hossain, Md Imam (MDPI, 2021)
Approximately 15–18% of crops losses occur as a result of animal pests, while weeds and microbial diseases cause 34 and 16% losses, respectively. Fungal pathogens cause about 70–80% losses in yield. The present strategies for plant disease control depend transcendently on agrochemicals that cause negative effects on the environment and humans. Nanotechnology can help by reducing the negative impact of the fungicides, such as enhancing the solubility of low water-soluble fungicides, increasing the shelf-life, and reducing toxicity, in a sustainable and eco-friendly manner. Despite many advantages of the utilization of nanoparticles, very few nanoparticle-based products have so far been produced in commercial quantities for agricultural purposes. The shortage of commercial uses may be associated with many factors, for example, a lack of pest crop host systems usage and the insufficient number of field trials. In some areas, nanotechnology has been advanced, and the best way to be in touch with the advances in nanotechnology in agriculture is to understand the major aspect of the research and to address the scientific gaps in order to facilitate the development which can provide a rationale of different nanoproducts in commercial quantity. In this review, we, therefore, described the properties and synthesis of nanoparticles, their utilization for plant pathogenic fungal disease control (either in the form of (a) nanoparticles alone, that act as a protectant or (b) in the form of a nanocarrier for different fungicides), nano-formulations of agro-nanofungicides, Zataria multiflora, and ginger essential oils to control plant pathogenic fungi, as well as the biosafety and limitations of the nanoparticles applications.